Evaluation of interthalamic adhesion size as an indicator of brain atrophy in dogs with and without cognitive dysfunction. Issue 5 (13th July 2017) - Noh, Daji; Choi, Sooyoung; Choi, Hojung; Lee, Youngwon; Lee, Kija
Abstract: Interthalamic adhesion thickness has been previously described as a parameter for quantifying canine brain atrophy and hypothesized to correlate with brain height or ventricular size. However, studies testing this hypothesis are lacking. This retrospective cross‐sectional study aimed to compare interthalamic adhesion thickness, interthalamic adhesion thickness/brain height ratio, and interthalamic adhesion thickness/brain height ratio/lateral ventricle to brain height ratio values in dogs with and without cognitive dysfunction. Medical records for dogs meeting the following inclusion criteria were retrieved from two hospitals: available brain magnetic resonance imaging (MRI) or computed tomography (CT) studies, no cerebral parenchymal lesions, and no prior neurological treatment. For each included dog, values of interthalamic adhesion thickness, interthalamic adhesion thickness/brain height ratio, and interthalamic adhesion thickness/brain height ratio/lateral ventricle to brain height ratio were measured by one observer from transverse CT or MRI images and a consensus was reached. A total of 113 dogs met inclusion criteria. Dogs were divided into three groups based on the following criteria: Young group (no cognitive dysfunction, <9‐year‐old, n = 43), Aging group (no cognitive dysfunction, ≥9‐year‐old, n = 61), and Dementia group ( n = 9). All three parameters were significantly lower in the dementia group than in the Young and Aging groups. In the Young and Aging groups, there was significant negative correlation of all three parameters with age and positive correlation of interthalamic adhesion thickness and interthalamic adhesion thickness/brain height ratio/lateral ventricle to brain height ratio with body weight, while there was no correlation of interthalamic adhesion thickness/brain height ratio with body weight ( P < 0.05). There were no differences in all three parameters according to skull type or gender. Findings from the current study supported the use of interthalamic adhesion thickness, interthalamic adhesion thickness/brain height ratio, and interthalamic adhesion thickness/brain height ratio/lateral ventricle to brain height ratio for quantifying brain atrophy in dogs with cognitive dysfunction.